Persepsi Masyarakat terhadap Adanya Penangkaran Rusa untuk Mengetahui Potensi Pemanfaatan Daging Rusa di Penangkaran Rusa Wana Wisata, Buana Jaya, Tanjung Sari, Bogor - Eva Oktaviani; Yaya Rayadin; Chandradewana Boer; Paulus Matius; Emi Purwanti; Rachmad Budiwijaya Suba (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Efforts to protect nature is one of the main things and is quite important in order to maintain all levels of life in this universe. Conservation of nature is the main thing that is most influential for humans to survive, but as time goes by, the existence of nature is increasingly threatened. Preserving nature can be done in situ and ex-situ. One of the efforts in preserving nature ex-situ can be done with captivity efforts so that it can overcome the level of extinction. The research was carried out using a descriptive method with a cross-sectional approach in several stages, namely the interview was conducted by giving several questions to the respondents in the form of a questionnaire and there were 25 women and 36 men as respondents who gave opinions regarding the management of deer breeding and the use of venison. in West java. The results of interviews conducted from 61 respondents produced the following data, namely 67.2% agreed about the captive breeding program, 59% of people were interested in the captive breeding program as a tourist attraction, 70.5% of people admitted that deer meat could be consumed, 80.3% claimed that they had never consumed venison, 21.3% knew the benefits of venison, 42.6% admitted that they knew the law regarding illegal deer capture and 24.6% admitted that they knew the law regarding illegal hunting. This research is expected to be a reference for captive managers in Wana Wisata to obtain information about the success of deer breeding and the potential use of deer meat.